2018
DOI: 10.1111/mcn.12687
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of exclusive breastfeeding among immigrant and Canadian‐born Chinese women

Abstract: Breastfeeding is the optimal method for infant feeding, yet migrant women may be at risk for suboptimal exclusivity rates. In a cohort of immigrant and Canadian-born Chinese women, our objectives were to (a) describe patterns and prevalence of exclusive breastfeeding at 1, 3, and 6 months postpartum; (b) identify risk and protective factors associated with exclusivity; and (c) examine potentially differential importance of these factors across this 6-month period. This was a prospective study of 565 immigrants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
4
22
1
Order By: Relevance
“…In this study with a high proportion of maternal employment and only 10 weeks of mandated maternity leave in Hong Kong, returning to work has been shown to be strongly associated with overall breastfeeding duration [23]. A local study show that approximately 85% of employed new mothers return to full-time employment before 10 weeks postnatal and 88% work 40 hours per week or more [24]. Therefore, most pregnant women make plans about returning to work before giving birth and their ability to combine breastfeeding and employment is likely reflected in their intended duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 63%
“…In this study with a high proportion of maternal employment and only 10 weeks of mandated maternity leave in Hong Kong, returning to work has been shown to be strongly associated with overall breastfeeding duration [23]. A local study show that approximately 85% of employed new mothers return to full-time employment before 10 weeks postnatal and 88% work 40 hours per week or more [24]. Therefore, most pregnant women make plans about returning to work before giving birth and their ability to combine breastfeeding and employment is likely reflected in their intended duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 63%
“…Educated mothers with previous breastfeeding experience and those living in Hong Kong for a shorter period of time were more likely to achieve participant individual goals. These characteristics were also frequently associated with a longer breastfeeding duration in other studies [18,19]. Although these are non-modifiable characteristics, additional breastfeeding support should be provided to less educated first-time mothers both during the postnatal hospitalization and after hospital discharge to help mothers achieve their individual breastfeeding goals.…”
Section: Discussionmentioning
confidence: 85%
“…Educated mothers with previous breastfeeding experience and those living in Hong Kong for a shorter period of time were more likely to achieve participant individual goals. These characteristics are also frequently associated with a longer breastfeeding duration in this and other populations [22][23][24][25]. Although these are nonmodifiable characteristics, additional breastfeeding support should be provided to less educated firsttime mothers both during the postpartum hospitalization and after hospital discharge to help mothers achieve their individual breastfeeding goals.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have shown that early formula supplementation directly undermines the initiation and duration of breastfeeding [24,30,35]. Early breastfeeding initiation after birth, minimizing separation between mother and baby, and support and advice to minimize maternal anxiety over perceived insufficient milk supply can help to reduce unnecessary formula supplementation during the postnatal hospital stay [36].…”
Section: Discussionmentioning
confidence: 99%